Standards-the international picture : halal standards accreditation mechanism. - Kayadibi, Saim (2012)
A new mechanism is needed for the sustainability of our own values in the global economic life since we live in a global world. The world is now becoming a single market system controlled by those who establish their own values and standards. Necessary preparations should be made as quickly as possible on this arena. Unfortunately, the whole world is facing now the most comprehensive post modern colonialism with a costless way. Those who set the rules, control the game. For that reason, there must be a transform of mentality from locality towards universality in every kind of fields. There are many companies that route the international standard-settings in order to control the world trade and financial activities for their own benefits. Their main goal is to create a mechanism that the certified and accredited goods by them will only be distributed in the world market, like a multi-national company SGS based in Sweden, which has estimated USD 6 billion turn over annually. It has 70,000 employees; they operate a network of more than 1,350 offices and laboratories around the world. Besides this there are many international standard companies based in France, Germany, USA, Sweden etc. All these Western originated companies’ annual turnover is more than 20 billion dollars. These standard companies get all the annual revenues of 1000/2. Not only taking your money for membership but also they decide which products should be sold in the market. Without their certificates your products hardly go to the world market. The local standards like TSE, MQA, EQA, SQA, etc. have nothing to do with that and have no role in decision making. Therefore, establishing a global accreditation mechanism in OIC countries is essential that requires the fulfilment of darurah (necessary) concept. As the definition of fiqh indicates “a person’s knowledge of his rights and obligations”, SMIIC of OIC, established in October 2010, has taken initiatives of fulfilling this holy responsibility bringing the benefit and avoiding the harm from the Ummah. Immediately after that the standards of SMIIC has been established in May 2011, accordingly TSE adopted it issuing certificates. It’s an unavoidable reality that the halal industry is large enough not to be underestimated and it is continuously growing market worth an estimated US 2 trillion a year. Therefore, the standards and the standardization as well as the halal standards accreditation mechanism should also be considered from the view point of the concept of Maqasid al-Shari’ah (High Objectives of the Lawgiver) in order to highlight its vitality and role in the global games. Although many countries, like governments of Turkey, Malaysia, UK, Thailand, Indonesia, USA, Germany, Sweden, Europe, Singapore, Canada, South Africa, Australia, China, Philippines and India, have established halal certification institutions, the Halal Monitoring Committee (HMC), the Muslim Council of Britain (MCB), Department of Islamic Development of Malaysia(JAKIM), Islamic Society of North America (ISNA), Islamic Food and Nutrition Council of America (IFANCA), International Halal Integrity (IHI), Islamic Chamber of Commerce and Industry (ICCI), World Halal Council (WHC), World Halal Foundation (WHF), etc. there is no such international standards to for all to represent them. Therefore, it is extremely necessary for countries to collectively agree on one global Halal Standard under the leadership of OIC. This paper will then discuss firstly international standards and standardization with their roles in the global economic activities, considering them from the view point of the concept of Maqasid al-Shari‘ah (High objectives of the Lawgiver). Secondly halal standards and accreditation mechanism will also be explored through bringing current realities in the Muslim world as well as the global arena. Keywords: Standards; Accreditation Mechanism; Halal Industry; Maqasid al-Shari’ah; Post Modern Colonialism.